Homology of the gonostylus parts in crane flies, with emphasis on the families Tipulidae and Limoniidae (Diptera, Tipulomorpha) - Ribeiro, Guilherme Cunha (Zootaxa, 2006)
The study of the morphology of the gonostylus – a structure of major importance for the taxonomy and systematics of crane flies – has shown that the terminology currently applied to the branches of this organ in Tipulomorpha and its implied primary homology hypothesis are inconsistent in the different families. In this paper, such inconsistencies are discussed, some basic criteria for the proper recognition of the homologous parts are given, and a revised nomenclatural system is proposed. The terms “clasper of gonostylus” and “lobe of gonostylus” are proposed for the gonostylar branches on the basis of the known functions of these structures.